From Panathenaic procession to Ara Pacis of August Discipleship and identity (Iter, 2022)
Rome was heir to Greek culture. From it the Romans learnt poetry, literature, philosophyand art. But Román creations, though inspired by the Greek genius, always expressed somethingoriginal and unique. Such is also the case with sculpture. A contrast betw’een the Parthenon sPanathenaic procession and the bas-relief on the Ara Pacis brings out the profound continuityof ancient art, and at the same time the strong and distinctive personality of these peoples.
Keywords: Ara Pacis, Panathenaic procession, Greek legacy, Román culture